2004
DOI: 10.1002/app.13487
|View full text |Cite
|
Sign up to set email alerts
|

Glycidyl methacrylate–grafted linear low‐density polyethylene fabrication and application for polyester/polyethylene bonding

Abstract: ABSTRACT:The grafting of glycidyl methacrylate (GMA) onto linear low-density polyethylene (LLDPE) was investigated. The grafting was performed by free-radical grafting in the melt state in a twin-screw extruder using an organic peroxide as initiator. The effect of initial GMA and peroxide concentration, styrene comonomer addition, as well as initial resin viscosity, on the final content in grafted moieties, unbound homopolymer, and unreacted monomer was assessed. The effect of process parameters such as flow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 38 publications
3
23
0
3
Order By: Relevance
“…Awkwardly, however, the conversion of GMA grafting reaction on PP backbone was not sufficient even with excessive amount of peroxide in the system [31]. It was found that introduction of styrene, as comonomer, enhances grafting yield, particularly at equimolar concentration with reactive monomer [32][33][34]. In this regard, GMA concentration, peroxide concentration, and melt-processing time were optimized based on experimental, classical, and artificial intelligence-based methodologies to proceed grafting reaction of GMA on high-density polyethylene with minimum disturbance of crosslinking reactions [24].…”
Section: Introductionmentioning
confidence: 94%
“…Awkwardly, however, the conversion of GMA grafting reaction on PP backbone was not sufficient even with excessive amount of peroxide in the system [31]. It was found that introduction of styrene, as comonomer, enhances grafting yield, particularly at equimolar concentration with reactive monomer [32][33][34]. In this regard, GMA concentration, peroxide concentration, and melt-processing time were optimized based on experimental, classical, and artificial intelligence-based methodologies to proceed grafting reaction of GMA on high-density polyethylene with minimum disturbance of crosslinking reactions [24].…”
Section: Introductionmentioning
confidence: 94%
“…Previous work in our laboratory 8 also showed that p-benzoquinone, triphenyl phosphate, and tetrachloromethane were good inhibitors for crosslinking of LDPE. Recent work made by Pesneau et al 9 who studied grafting glycidyl methacrylate onto linear low density polyethylene (LLDPE) reported that the high graft degree (GD) could be obtained by a proper selection of the feed composition and process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalized PE are also widely recognized as novel, potential additives to improve the compatibilizing influence in binary or multicomponent polymer blends, and they are finding increasing use in reactive blending. 2,6 Most of the studies carried out in the melt so far have focused on the influence of reaction parameters, the degree of functionalization and optimal properties achieved, 3,[7][8][9] and on the determination of the nature of grafted unit. 10 Melt processing of PE is often accompanied by side reactions such as crosslinking of PE and homopolymerization of graft monomer and many efforts have been made to enhance degree of grafting and reduce the side reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Auxiliary monomer 10 Maleimide derivatives 11 Methacrylate esters 12 Acetoacetoxy methyl methacrylate 11 Glycidyl methacrylate 13,14 Acrylate esters 15 Ricinoloxazoline maleate 16 Vinylsilanes 17…”
Section: Styrenementioning
confidence: 99%